FACEBOOK LEAKS: HOW DOES INDONESIAN LAW REGULATE IT? - Arifin, Ridwan; Ratna Atika, Taza (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2021)
Along with the development in the world of technology, especially in the internet sector, which has provided so many benefits and advantages and conveniences for many people, in addition to these advantages there are also developments in negative aspects, the existence of risks, and the negative impact of its misuse by parties who not responsible. Some time ago the Indonesian people were quite troubled by the emergence of cases of leakage of personal data of Facebook users. The personal data leakage scandal of Facebook users that has been broken into by the analytical research firm Cambridge Analytica is targeting the entire world population, one of which is Indonesia. Many people are wondering who is to blame and responsible for this case. What is the cause of this case and can it be prevented.